Hearing aids for mild to moderate hearing loss in adults - Ferguson, Melanie A (Cochrane Database Syst Rev, 2017)
BACKGROUND: The main clinical intervention for mild to moderate hearing loss is the provision of hearing aids. These are routinely offered and fitted to those who seek help for hearing difficulties. By amplifying and improving access to sounds, and speech sounds in particular, the aim of hearing aid use is to reduce the negative consequences of hearing loss and improve participation in everyday life. OBJECTIVES: To evaluate the effects of hearing aids for mild to moderate hearing loss in adults. SEARCH METHODS: The Cochrane ENT Information Specialist searched the ENT Trials Register; the Cochrane Register of Studies Online; MEDLINE; PubMed; EMBASE; CINAHL; Web of Science; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 23 March 2017. SELECTION CRITERIA: Randomised controlled trials (RCTs) of hearing aids compared to a passive or active control in adults with mild to moderate hearing loss. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures expected by Cochrane. The primary outcomes in this review were hearing‐specific health‐related quality of life and the adverse effect pain. Secondary outcomes were health‐related quality of life, listening ability and the adverse effect noise‐induced hearing loss. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. MAIN RESULTS: We included five RCTs involving 825 participants. The studies were carried out in the USA and Europe, and were published between 1987 and 2017. Risk of bias across the studies varied. Most had low risk for selection, reporting and attrition bias, and a high risk for performance and detection bias because blinding was inadequate or absent. All participants had mild to moderate hearing loss. The average age across all five studies was between 69 and 83 years. The duration of the studies ranged between six weeks and six months. There was a large beneficial effect of hearing aids on hearing‐specific health‐related quality of life associated with participation in daily life as measured using the Hearing Handicap Inventory for the Elderly (HHIE, scale range 1 to 100) compared to the unaided/placebo condition (mean difference (MD) ‐26.47, 95% confidence interval (CI) ‐42.16 to ‐10.77; 722 participants; three studies) (moderate‐quality evidence). There was a small beneficial effect of hearing aids on general health‐related quality of life (standardised mean difference (SMD) ‐0.38, 95% CI ‐0.55 to ‐0.21; 568 participants; two studies) (moderate‐quality evidence). There was a large beneficial effect of hearing aids on listening ability (SMD ‐1.88, 95% CI ‐3.24 to ‐0.52; 534 participants; two studies) (moderate‐quality evidence). Adverse effects were measured in only one study (48 participants) and none were reported (very low‐quality evidence). AUTHORS' CONCLUSIONS: The available evidence concurs that hearing aids are effective at improving hearing‐specific health‐related quality of life, general health‐related quality of life and listening ability in adults with mild to moderate hearing loss. The evidence is compatible with the widespread provision of hearing aids as the first‐line clinical management in those who seek help for hearing difficulties. Greater consistency is needed in the choice of outcome measures used to assess benefits from hearing aids. Further placebo‐controlled studies would increase our confidence in the estimates of these effects and ascertain whether they vary according to age, gender, degree of hearing loss and type of hearing aid.